A Collaborative Approach in Teaching Descriptive Text Writing: A Study on Grade 10 Students of ESTV-IT 28 Novembro Dili Timor Leste - Francisco Saramento Morais; Ida Widia; Suci Sundusiah (Dinasti Publisher, 2025)
This study aims to explore the implementation of a collaborative approach in teaching descriptive text writing to grade 10 students in one of the public schools ESTV-IT 28 Dili Timor Leste. The problem behind this study is the students' low ability to write descriptive text effectively, which is characterized by a lack of ideas, poor paragraph structure, and weak use of vocabulary. The collaborative approach is believed to address these problems. by providing space for students to discuss, give feedback, and build mutual understanding in the writing process. This research used a qualitative approach with a case study method. Data were collected through classroom observations, in-depth interviews with teachers and students, and document analysis in the form of student writing results and learning tools. The results show that the implementation of collaborative approach can increase students' involvement in the learning process, strengthen critical thinking and cooperation skills, and produce more structured and expressive writing. Despite challenges such as unequal participation in groups and time constraints, teacher mentoring strategies and the use of peer feedback proved effective in supporting the collaborative process. This study makes an important contribution to the development of collaboration-based writing teaching strategies, especially in descriptive text learning. The results of this study are expected to be a reference for teachers in designing learning that is contextual, participatory, and in accordance with the needs of 21st century students.